Analisis Kesalahan dalam Penggunaan Huruf Kapital dan Tanda Baca pada Teks Karangan Sederhana Siswa Kelas III SDN Banjarsari - Sari, Widiya Kemala; Merianti, Lia; Azhar, Aufaa Nabilla (Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This research is motivated by the errors seen when students write capital letters and punctuation marks in a sentence that is made. This research was conducted using a method that is descriptive qualitative, where this method involves direct research, in observing an object under study, which aims to examine errors when using capital letters and punctuation marks in an essay that has been made by students and female students. The data collection from the research results is explained together with the location of the errors and explained in words. In this study, the subjects studied were third grade students of SDN Banjarsari 113 with a total of 32 students and third grade teachers of SDN Banjarsari 113. The research employs documentation, interviews, and observation as methods for collecting data. Data review was carried out by collecting data, data selection process, data presentation, and conclusion drawing. The results of the research conducted found several errors in the application of capital letters and punctuation marks. These errors include the writing and placement of capital letters in a sentence, mistakenly placing punctuation marks in a sentence made, and errors in the application of capital letters usually occur in the initial word which is the first sentence, in new sentences, in sentence substitutions, place names and names of people. The cause of these errors is because students still write casually, do not pay attention to the proper application of capital letters and punctuation marks, do not understand the use of capital letters and punctuation marks themselves, and are unfocused or do not pay attention when the teacher explains, then forget the proper writing of capital letters and punctuation marks, so it is wrong when applying them.